Transient asymptomatic hepatitis B surface antigenemia following recombinant Recombivax B hepatitis B vaccine in a 42-year-old ESRD patient on maintenance hemodialysis - Macaulay Amechi Chukwukadibia Onuigbo; Catherine Kress; Carol Webb; Nneoma Agbasi (Society of Diabetic Nephropathy Prevention, 2018)
A 42-year old Caucasian end-stage renal disease (ESRD) male patient with past medical history including diabetes, hypertension, pulmonary hypertension (RVSP of 53 mm Hg) and tobacco use tested positive for hepatitis B surface antigen (HBsAg) after a routine blood screening test using an enzyme immunoassay (EIA) method. He however was otherwise asymptomatic for any symptoms of hepatitis. On further review, we confirmed that he had received an intramuscular dose of Recombivax (Merck) vaccine, 1 mL = 40 µg, 5 days previously. Follow up liver panel test was unremarkable with normal bilirubin and transaminases. Repeat serology testing at Mayo Clinic, Rochester the next day for a confirmatory neutralizing antibody assay test was negative for HBsAg. Furthermore, hepatitis B core IgM antibody, hepatitis B surface antibody, hepatitis B surface antibody qualitative, hepatitis B surface antibody quantitative test <0.1 (<8.0 mIU/mL), hepatitis B e antibody and hepatitis B core total antibody tests all subsequently returned negative. This is the second case of transient postvaccination HbSAgenemia observed in our hemodialysis Unit in Northwestern Wisconsin in the last 7 years. Once again, as we posited in our 2010 report, we reemphasize previous recommendations that patients who receive hepatitis B vaccinations should not be screened for HBsAg less than 4 weeks following a hepatitis B vaccination.